Fluid constellation : hybrid dynamics of the Irish bottled water industry - Dunne, Sean (Trinity College (Dublin, Ireland). Department of Sociology, 2008)
This dissertation provides an analysis of the Irish bottled water industry by constructing a revised version of Adorno's method of immanent critique. It incorporates the negative dialectical approach advanced by Adorno and revises it with the nonmodern perspective argued by Bruno Latour and other Actor Network Theorists. The strategy employed throughout the research involved the juxtaposition of marketing, regulatory and industrial networks of practice and demonstrated the various attractions and aversions that exist between each network. This framework was designed as an attempt to unravel the sociohistorical significance found within Irish bottled water by analysing the many networks, actants and ideologies that contribute to the production of Irish bottled water.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin